2020
DOI: 10.3389/fphys.2020.00850
|View full text |Cite
|
Sign up to set email alerts
|

Lipophagy Impairment Is Associated With Disease Progression in NAFLD

Abstract: Non-alcoholic fatty liver disease (NAFLD) is the most common cause of chronic liver disease in Western countries and is associated with aging and features of metabolic syndrome. Lipotoxicity and oxidative stress are consequent to dysregulation of lipid metabolism and lipid accumulation, leading to hepatocyte injury and inflammation. Lipophagy consists in selective degradation of intracellular lipid droplets by lysosome and mounting evidence suggests that lipophagy is dysregulated in NAFLD. Here we demonstrate … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
65
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 89 publications
(68 citation statements)
references
References 44 publications
2
65
0
1
Order By: Relevance
“…The number of hepatocytes with p62 aggregation correlated positively with the number of autophagic vesicles and various NAFLD severity outcomes (including NAS, fibrosis, and serum alanine aminotransferase levels). An even more recent study confirmed this finding by immunohistochemistry staining of liver biopsies of 59 patients with steatohepatitis, In these biopsies, there was increased accumulation of p62 clusters and alterations in autophagy-related gene expression that correlated with NAS and fibrosis stage ( 66 ).…”
Section: Clinical Studiesmentioning
confidence: 69%
See 1 more Smart Citation
“…The number of hepatocytes with p62 aggregation correlated positively with the number of autophagic vesicles and various NAFLD severity outcomes (including NAS, fibrosis, and serum alanine aminotransferase levels). An even more recent study confirmed this finding by immunohistochemistry staining of liver biopsies of 59 patients with steatohepatitis, In these biopsies, there was increased accumulation of p62 clusters and alterations in autophagy-related gene expression that correlated with NAS and fibrosis stage ( 66 ).…”
Section: Clinical Studiesmentioning
confidence: 69%
“…Several human association studies have demonstrated that mutations in autophagy-related genes increase the risk of NAFLD development. A recent study using both pre-clinical models and patient material demonstrated that advanced stage NAFLD is associated with greater impairments of hepatic autophagy ( 66 ) and an association was also found between the autophagy-related GTPase family M ( IRGM ) gene and increased susceptibility of NAFLD in obese children ( 84 ). In vitro experiments in HepG2 cells revealed that IRGM knockdown inhibited the autophagic flux and increased LD content while overexpression of IRGM decreased LD content, highlighting its role in lipophagy.…”
Section: Lipophagy: the Fifth Pathway Involved In Non-alcoholic Fattymentioning
confidence: 99%
“…Autophagic degradation of LDs (lipophagy) is commonly thought necessary for TG turnover and FFA β-oxidation, which prevents lipotoxicity and further progression of the disease (Singh and Cuervo, 2011;Carotti et al, 2020). Thus, models with impaired autophagy activation are expected to accumulate more TGs in hepatocytes after an obesogenic diet, while activation of autophagy should prevent or improve this outcome.…”
Section: Nutritional Overload Modelsmentioning
confidence: 99%
“…The protective role of autophagy against steatosis development in NAFLD models is mainly associated with TG hydrolysis by lipophagy activation (Carotti et al, 2020). However, it is possible that autophagic activity may affect lipid metabolism directly or indirectly by different mechanisms.…”
Section: Further Considerationsmentioning
confidence: 99%
“…Autophagy has been shown to be a key regulator in the control of lipid metabolism [16], and the degradation of lipids via autophagy (lipophagy) has been revealed as a key pathway for the regulation of intracellular lipid content in hepatocytes [17]. Impaired autophagy/lipophagy during aging can lead to excessive tissue lipid accumulation such as hepatic steatosis and progression of NAFLD [17][18][19]. Autophagy can be modulated by ER stress, and it has been described that impaired autophagic flux is associated with increased ER stress during NAFLD development [20].…”
Section: Introductionmentioning
confidence: 99%